NETWORKED ELECTRONIC LIBRARY OF THE FEDERAL UNIVERSITIES: THE NEW FORMAT OF THE RESEARCH AND EDUCATION SPACE - Elena V. Kudryashova; Larissa A. Morschikhina (Высшее образование в России)
The leading Russian universities who are actively developing today new forms of networking are able not only to create a large volume of the relevant electronic content, but also to change the system of production and consumption of knowledge.An aim of the project «Networked electronic library of the federal universities» is to create a common virtual space for access providing to educational, scientific, methodological information.Distinctive features of the project are: the creation of a technological platform and organizational methods for the development and use of the joint educational programs of the federal universities; an automation of key business processes which are necessary for the organization of the legitimate placement of scientific and educational literature in open access and for the commercialization of the full-text electronic content of the federal universities; an implementation of additional services for advancement of the federal universities in the scientometric databases and for monitoring of the distant educational process.